Qualitative and quantitative evaluation of a standardized training model for improving patients' ability to use inhalers - Huang, Yuwen; Miao, Fangzhou; Dai, Yunjian; Chang, Cuie; Zhang, Xiaoyu; Dai, Haibin (Frontiers in Public Health, 2023)
Objective: Training contributes to the effectiveness of aerosol inhalation therapy. However, qualitative and quantitative evaluation of effective training methods is rarely reported. This study aimed to evaluate the effectiveness of a standardized training model by pharmacists based on verbal instruction and physical demonstration in improving patients' ability to use inhalers using qualitative and quantitative methods. Risk or protective factors affecting correct inhaler use were also explored. Methods: 431 Outpatients with asthma or COPD were recruited and randomly divided into a standardized training group (n=280) and a usual training group (control group, n=151). A framework of qualitative (e.g., multi-criteria analysis) and quantitative comparisons (percentage of correct use (CU%), percentage of complete error (CE%), and percentage of partial error (PE%)) was established to evaluate the two training models. In addition, the changes of key factors (age, education level, adherence, device type, etc.) influencing patients' ability to use inhalers of two models were observed. Results: The multi-criteria analysis showed that the standardized training model had comprehensive advantages in qualitative indicators. The average correct use percentage (CU%) of the standardized training group was significantly higher than that of the usual training group (77.6% vs. 35.5%). A stratified analysis further demonstrated that the ORs (95%CI) in the usual training group of age and educational level was 2.263 (1.165-4.398) and 0.556 (0.379-0.815), while in the standardized training group, age and educational level were not the key factors influencing the ability to use inhaler devices (P>0.05). Logistic regression analysis demonstrated that standardized training was a protective factor for inhalation ability. Conclusion: These findings indicate that the framework of qualitative and quantitative comparisons could be used to evaluate training models, and the standardized training model by pharmacists can significantly improve patients' ability to use inhalers correctly and address the influence of older age and lower education because of its methodological advantages. Further studies with more extended follow-up are needed to validate the role of the standardized training model by pharmacists in the correct use of inhalers. Clinical Trial Registration: chictr.org.cn; registration number: ChiCTR2100043592 (23-02-2021).